Jetlag. - Universidade de Lisboa; Batista, Tiago; Bruxo, Isabel Maria Maçana da C.; Carvalho, Luis Silva; Fernandes Dias, José Antonio B.; Guerra, José; Mendonça, Antonio Cadima; Nobre, Salao (Lisboa : Universidade de Lisboa, 1996)
Watkins, Andrew-Hayes ; Ferreira, Angela ; de Sousa, Antonio ; Mateus, Cristina ; Diana ; Brito, Fernando ; Carlos, Isaac ; Provoost, Ivo ; Noronha, Joel ; Guerra, José ; Kinnon, karen Mc ; Richter, Kattrin ; Schaeffer, Laura ; Poppe, Mariel ; Leal, Miguel ; Carmona, Paulo ; Cabral, Pedro ; Clode, Pedro ; Portugal, Pedro ; Denicolai, Simona ; Batista, Taigo ; Domingos, Tiny ; Johaensen, Torben
biografie
Jetlag, Universidade de Lisboa, 15 de Junho a 15 de Julho de 1996
Portugees
Portugees & Engels
boek